Biomechanics of elite recumbent handcycling: a case study - Litzenberger, S.; Mally, F.; Sabo, A. (Sports Engineering, 2016)
In the presented research, a kinematic and electromyographic study was performed on one world-class male elite handbiker (UCI class H3.2). Activity of 14 muscles of the upper body were measured with surface electromyography (EMG), and a motion analysis of the athlete`s movement was performed concurrently for different backrest positions, crank lengths, and crank heights at three power levels (130, 160 and 190W). Kinematics in terms of elbow and wrist angle, muscular on-off timing, EMG amplitudes, and integrated EMG were calculated. Results showed that little changes occurred for kinematic parameters and changes in position led to a shift in muscular timing. However, no indication for immediate improvement to the athlete`s preferred original position could be observed.